Analisis Nutrisi Sereal dari Ampas Kelapa dan Ampas Susu Kedelai: Nutritional Analysis of Cereals from Coconut Pulp and Soy Milk Pulp - Sari, Nurfita; Sumarni, Ni Ketut; Bahri, Syaiful; Nurhaeni; Amar, Aini Auliana; Syamsuddin; Jusman (KOVALEN: Jurnal Riset Kimia, 2023)
Coconut pulp and soy milk pulp flour can be combined to reduce the use of wheat flour in the manufacture of cereals. The high fiber and protein content of coconut and soy milk pulp will improve the quality of cereals. The aim of this study was to obtain the mass ratio of coconut and soy milk pulp flour which produces cereals with high nutritional value. The ratio of coconut and soy milk pulp flour used was 0:100; 25:75; 50:50; 75:25; and 100:0 (w/w). Cereal quality was determined based on the value of carbohydrate, protein, fat, fiber, water, and ash content. The results showed that the protein, fat, water, and ash content met the SNI standard, while the fiber content was still higher than the maximum SNI limit. Statistically, the treatment of the ratio of coconut and soy milk pulp flour had a significant effect on all cereal quality parameters (sig. 0.00 < Î± (0.05)). The high cereal protein content was found in all levels, namely in the range of 14.29-21.14%, while the fat content was in the range of 17.8-34.41%. The use of a 0:100 ratio produces carbohydrate content that meets SNI, which is more than 60%. The use of a combination of coconut pulp and soy milk pulp for the manufacture of cereals that needs to be developed is 25:75 (w/w), however still needs further modifications to reduce fiber content and increase the carbohydrate content.